Cuantificación de colágeno tipo I y tipo III en el corazón de bovinos con deficiencia secundaria de cobre - Nicastro, C.N. (2021)
Copper deficiency is an important disease of cattle in our country. One manifestation of copper deficiency\nis falling disease, characterized by heart lesions that lead to heart failure. The aim of this work was to study if there were any changes in the amount of collagen type I and type III in the connective tissue of the heart in cattle with secondary copper deficiency. Paraffin blocks from 18 myocardial samples of 18 Holando Argentino calves, divided into 2 groups (control group and deficient group), were used. Sections were colored with the picrosirius red technique, and examined under polarized light, in order to discriminated type I collagen fibers from type III collagen fibers. No statistically significant differences were found between the two groups for the percentage of collagen type I (p = 0.7409) and type III (p = 0.5227), nor for the relation between both collagens (p = 0.9623). It is probable that the deficiency was not extended enough to induce alterations in the amount of type I and type III collagen fibers of the Cu-deficient bovines.\n